Estrogen regulation of the avian transferrin gene in transgenic mice. - Hammer, R E (1986)
The intact chicken transferrin gene was microinjected into fertilized mouse eggs, and the resulting transgenic animals were used to produce lines of mice containing integrated copies of the chicken gene. The levels of expression of the chicken gene were quantitated in various tissues, and the response of the gene to estrogen stimulation was measured after chronic or acute estrogen exposure. Two of the three mouse lines studied maintained stable levels of expression in successive generations of offspring, and the third line had two- to threefold-higher levels in offspring than in the original parent. In the third line, the original transgenic parent was found to be a mosaic. The chicken transferrin gene was expressed at 10- to 20-fold-higher levels in liver than in any other tissue; however, the levels of chicken transferrin mRNA in kidney were higher than expected, indicating that the tissue specificity was only partial. In all three lines, the foreign gene was induced by estrogen administration. After 10 days of estrogen administration, there was a twofold increase in both transferrin mRNA and transcription of the chicken transferrin gene. A single injection of estradiol led to a fourfold increase in transferrin mRNA synthesis at 4h. As a control the levels of mouse albumin were measured, and both the level of albumin mRNA and its rate of transcription declined about twofold after estrogen administration. Our results indicate that the intact chicken gene with 2.2 kilobases of 5' flanking sequence contains signals for both tissue specificity and steroid regulation that can be recognized in mice.